Revision of the genus Scapomegas Lacordaire, 1854 (Coleoptera: Histeridae: Omalodini) - Leivas, Fernando W. T.; Bicho, Carla L.; Degallier, Nicolas; Moura, Daniel P. (Zootaxa, 2012)
The Neotropical genus Scapomegas Lacordaire, 1854 is revised. All three species are illustrated and keyed, and new distribution records and ecological data are provided. Scapomegas can be recognized, among other characters, by a rudimentary supraorbital stria indicated posteriorly; the base of the antennal scapus abruptly expanded and approximately parallel-sided from there to apex; the prosternum slightly emarginated posteriorly; and the anterior, middle and hind tibiae with a row of spines on the outer margin and another on the submarginal region. Scapomegas aurifer Marseul, 1887 and S. gibbus Marseul, 1855 are associated with the Atlantic Forest biome and have usually been found in rotten meat, whereas S. auritus Marseul, 1855 is associated with the Amazon biome and found in carcasses and dendrophilic mushrooms.